2018
DOI: 10.1021/acssuschemeng.7b03684
|View full text |Cite
|
Sign up to set email alerts
|

Deep Eutectic Solvents as Suitable Electrolytes for Electrochromic Devices

Abstract: The development of chloride free Deep Eutectic Solvents (DES) based on lithium acetate, triflate, bistriflimide, and sodium triflate combined with glycerol, ethylene glycol, and polyethylene glycol (PEG400) as suitable electrolytes was successfully applied in electrochromic devices (ECD). Reversible ECD incorporating selected DES as electrolyte and bipyridinium as electrochromic probes displayed a comparable performance to conventional systems, with slower transition times (2.5 times), improving the coloration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
45
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 73 publications
(50 citation statements)
references
References 63 publications
4
45
0
1
Order By: Relevance
“…They can be synthesized by simple mixing of the low‐cost and environmental friendly starting materials just heat up most of the times and without further purifications. Recently, we reported DES as low cost and green electrolytes for electrochromic devices . To the best of our knowledge, this is the first example of POM‐ILs combined with DES as electrolytes.…”
Section: Introductionmentioning
confidence: 82%
“…They can be synthesized by simple mixing of the low‐cost and environmental friendly starting materials just heat up most of the times and without further purifications. Recently, we reported DES as low cost and green electrolytes for electrochromic devices . To the best of our knowledge, this is the first example of POM‐ILs combined with DES as electrolytes.…”
Section: Introductionmentioning
confidence: 82%
“…A wide array of alcohols have been used so far as HBDs for DESs, 5 but to the best of our knowledge their mixtures with lithium salts have not been applied as electrolytes for batteries yet. A few reports investigate their application for electrochemical double layer capacitors, 146 or electrochromic devices, 7,152,153 giving some insights into their characterization for electrochemical applications. Cruz et al showed for instance that for the same lithium salt (LiCl or lithium iodide LiI) DESs containing G showed lower conductivity values than the EG analogues.…”
Section: Lithium Salts and Alcoholsmentioning
confidence: 99%
“…Our group reported electrochromic materials and respective devices based on transition metal oxides, Prussian blue systems,, conducting polymers, and viologen derivatives,, among others. Recently, we already reported the application of DES as green electrolytes for electrochromism ,…”
Section: Figurementioning
confidence: 99%